Estudio de la satisfacción de los usuarios luego de la adopción del Sistema Único de Acreditación en Salud, en el Centro Policlínico del Olaya (2012)
Knowing the degree of user satisfaction with a service, it is essential to guide decision sandactions to be followed by organizations in order to improve their performance. Regarding health services, this knowledge is more important, especially for those health institutions which have decided to implement the Sistema Único de Acreditación, which stands out as the best quality in service delivery and should therefore verify the impact they have on customer satisfaction; the assessment of user satisfaction is a complex process, not least of all because of the high subjectivity that this presents. The objective of this research is to identify the level of satisfaction and perception of the changes generated by the adoption of the Single System of Accreditation by external users of Olaya Polyclinic Center of Bogotá– CPO.The methodology followed by the Polyclinic yielded information on the state prior to the implementation of the Accreditation System and subsequent to this, in terms of user satisfaction. The design and implementation of a tool was also considered to identify the degree of knowledge that users of this Centre have regarding the system in question.The results show the effort the polyclinic has undertaken using constant and continuous work in quality, as well as the appreciations that users have about the Center and regarding the Unified Health Accreditation.